Control of ionization processes in magnetron sputtering system by changing magnetic field configuration - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Makhlai, V.A. (Вопросы атомной науки и техники, 2021)
This work is devoted to measuring the function of the distribution of charged particles of gas-discharge plasma in a magnetron sputtering system under conditions of non-potential “earth”. Measurements are carried out with the help of a three-electrode probe, which is installed in the cathode sputtering zone, with unsafe electrodes and housing. The selection of the analyzed particles was carried out through a screen located under floating potential. Effect of additional magnetic insulation anode of MSS МАG-5 on ion and electron distribution functions was investigated. Робота присвячена вимірюванню функції розподілу заряджених частинок газорозрядної плазми в магнетронній розпорошувальній системі в умовах непотенційної «землі». Вимірювання проведені за допомогою триелектродного зонду, який встановлено в зоні катодного розпилення, з незаземленими електродами і корпусом. Відбір досліджуваних частинок проводили через екран, розташований під плаваючим потенціалом. Досліджено вплив додаткової магнітоізоляції анода МРС МАГ-5 на функції розподілу іонів та електронів. Работа посвящена измерению функции распределения заряженных частиц газоразрядной плазмы в магнетронной распылительной системе в условиях непотенциальной «земли». Измерения проведены с помощью триэлектродного зонда, расположенного в зоне катодного распыления, с незаземленными электродами и корпусом. Отбор исследуемых частиц проводили через экран, находящийся под плавающим потенциалом. Исследовано влияние дополнительной магнитоизоляции анода МРС МАГ-5 на функции распределения ионов и электронов.